Early phylogenetic estimate of the effective reproduction number of SARS‐CoV‐2 - Lai, Alessia; Bergna, Annalisa; Acciarri, Carla; Galli, Massimo; Zehender, Gianguglielmo (Journal of medical virology, 2020)
To reconstruct the evolutionary dynamics of the 2019 novel‐coronavirus recently causing an outbreak in Wuhan, China, 52 SARS‐CoV‐2 genomes available on 4 February 2020 at Global Initiative on Sharing All Influenza Data were analyzed. The two models used to estimate the reproduction number (coalescent‐based exponential growth and a birth‐death skyline method) indicated an estimated mean evolutionary rate of 7.8 × 10−4 subs/site/year (range, 1.1 × 10−4‐15 × 10−4) and a mean tMRCA of the tree root of 73 days. The estimated R value was 2.6 (range, 2.1‐5.1), and increased from 0.8 to 2.4 in December 2019. The estimated mean doubling time of the epidemic was between 3.6 and 4.1 days. This study proves the usefulness of phylogeny in supporting the surveillance of emerging new infections even as the epidemic is growing. Highlights The aim of this study was to investigate the temporal origin, rate of viral evolution and population dynamics of SARS‐CoV‐2. The Bayesian approach used indicated a most probable origin of the epidemic between October and November 2019. The estimated effective reproductive number increased from 0.8 to 2.4 in December 2019 when the mean doubling time was about 4 days. This study proves the usefulness of phylogeny in supporting the surveillance of emerging new infections.